Tinjauan Hukum Pelanggaran Izin Traek (Studi Di Dinas Perhubungan Kabupaten Buton) - Hasirudin Hasri; Al Hiday Nur; Hayun Hayun; Rizwan Rizwan; Nanda Rosmaya (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Licensing for road transport is an effort to accommodate legal certainty and rights for road transport owners so that it can operate properly. Basically efforts to control licensing can also make a real contribution to Buton Regency's own-source revenue (PAD) in the service sector, thus making the Buton Regency Transportation Agency the main instrument in minimizing violations of route permits and order in public transportation in Buton district which It has quite intense traffic activity. This effort makes the people of Buton district orderly in the field of licensing in terms of transportation, indirectly this can be used as a measure of the success of the Buton Regency Transportation Service as one of the cogs of good government. Legal Review of Traek Permit Violations (Study at the Buton Regency Transportation Service), The main objectives of this research are (1) to find out technically how the arrangements are made by the Buton Regency Transportation Service in implementing route permits in Buton Regency; (2) To find out the factors that led to violations of route permits in Buton Regency and the forms of settlement that occurred.